Applying RMA for scheduling field device components - Liang, Peng; Arévalo, Gabriela Beatriz; Ducasse, Stéphane; Lanza, Michele; Schaerli, Nathanael; Wuyts, Roel; Nierstrasz, Oscar (2002)
PECOS is a collaborative project between industrial and research partners that seeks to enable component-based technology for a class of embedded systems known as "field devices". Results so far include a component model for field devices and a composition language for specifying connections between software components. Here we investigate the application of Rate Monotonic Analysis (RMA) to the problem of generating real-time schedules for compositions of field device components.
Este documento es producción intelectual de la Facultad de Informática-UNLP (Colección BIPA / Biblioteca.) -- Formato de archivo: PDF. -- Disponible también en línea (Cons. 3/04/2008)
ECOOP 2002 Workshop Reader, 2002.
Keywords: SISTEMAS DE TIEMPO REAL; DESARROLLO DE SOFTWARE BASADO EN COMPONENTES; RATE MONOTONIC ANALYSIS - RMA